2017
DOI: 10.1590/1413-81232017221.14222016
|View full text |Cite
|
Sign up to set email alerts
|

Trajetórias de mulheres vivendo com HIV/aids no Brasil. Avanços e permanências da resposta à epidemia

Abstract: Trajetórias de mulheres vivendo com HIV/aids no Brasil. Avanços e permanências da resposta à epidemiaTrajectories of women living with HIV/AIDS in Brazil. Progress and permanence of the response to the epidemic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 22 publications
0
11
0
4
Order By: Relevance
“…1 Currently, involvement of socially more vulnerable populations, non-homogeneous distribution of the disease among Brazilian regions, especially with increased numbers of notifications in small and medium-sized municipalities, and the growing number of HIV-infected women are hallmarks of this epidemic. [2][3][4] These characteristics indicate that the Brazilian healthcare system presents deficiencies with regard to prevention and treatment of HIV infection, especially in municipalities and population groups located in more distant and difficult-to-access areas, as occurs in northern Brazil. 1,2,[5][6][7] Over the last ten years, the northern region of Brazil has shown an upward trend in the rate of HIV/AIDS detection: 16.4 cases per 100,000 inhabitants were registered in 2007 and 23.6 cases per 100,000 inhabitants were registered in 2017 (an increase of 44.2%), with the state of Pará contributing an increase of 55%.…”
Section: Introductionmentioning
confidence: 99%
“…1 Currently, involvement of socially more vulnerable populations, non-homogeneous distribution of the disease among Brazilian regions, especially with increased numbers of notifications in small and medium-sized municipalities, and the growing number of HIV-infected women are hallmarks of this epidemic. [2][3][4] These characteristics indicate that the Brazilian healthcare system presents deficiencies with regard to prevention and treatment of HIV infection, especially in municipalities and population groups located in more distant and difficult-to-access areas, as occurs in northern Brazil. 1,2,[5][6][7] Over the last ten years, the northern region of Brazil has shown an upward trend in the rate of HIV/AIDS detection: 16.4 cases per 100,000 inhabitants were registered in 2007 and 23.6 cases per 100,000 inhabitants were registered in 2017 (an increase of 44.2%), with the state of Pará contributing an increase of 55%.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the low educational level tends to make it more difficult for the person to find a place in the job market (18) , which would explain the results found, according to which most pregnant women (46.8%) reported not having a paid job. Similar studies showed that HIV was more common among housekeepers and women who received low salaries for their work (2,4,(19)(20) .…”
Section: Discussionmentioning
confidence: 98%
“…Dessa forma, a efetivação da individualidade do cuidado humanizado é essencial às mães soropositivas, com a finalidade de prover meios para o enfrentamento das principais dificuldades vivenciadas por elas, com isso, tornase indispensável que os profissionais se aproximem da realidade dessas mulheres, ouvindo-as e permitindo que elas expressem todas as suas dúvidas 8 . Entretanto, para que haja adesão as consultas, são necessários, suportes psicossociais que contribuam para a aceitação do diagnóstico e elaboração de formas de convívio com a infecção que permitam o desfrute da vida e a continuidade dos projetos que lhe dão sentido 16 .…”
Section: Discussionunclassified